2020
DOI: 10.1177/0967391120960658
|View full text |Cite
|
Sign up to set email alerts
|

Studies on mechanical properties, dielectric behavior and DC conductivity of neodymium oxide/poly (butyl methacrylate) nanocomposites

Abstract: The current article aims to develop poly (butyl methacrylate) (PBMA) nanocomposites with enhanced electrical and mechanical properties by incorporating neodymium oxide (Nd2O3) nanoparticles between the PBMA chains. The morphological, thermal and structural profiles of the PBMA nanocomposites reinforced with different loading of Nd2O3 nanoparticles were investigated by scanning electron microscopy (SEM), X-ray diffraction (XRD) and thermogravimetric analysis (TGA). The SEM images revealed that the morphology of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 38 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…The tensile strength of material is diminished as a result of the nanoparticles failure to uniformly transmit stress from the polymer matrix. 32 The elongation at break is observed to be slightly reduced by the inclusion of nanoparticles, as shown in Table 1. This is due to the increased stiffness of the CPE nanocomposites.…”
Section: Resultsmentioning
confidence: 89%
“…The tensile strength of material is diminished as a result of the nanoparticles failure to uniformly transmit stress from the polymer matrix. 32 The elongation at break is observed to be slightly reduced by the inclusion of nanoparticles, as shown in Table 1. This is due to the increased stiffness of the CPE nanocomposites.…”
Section: Resultsmentioning
confidence: 89%
“…The blend of these polymers shows 466°C as degradation temperature. With the increasing filler content in the neat blend, T max is also increasing; it is reported that composite with the 30 wt% shows the 479.14°C degradation temperature, [ 52 ] thus the enhancement in thermal stability of the composite is because of the polymer and VCB filler interaction which restrict the diffusion the volatile component.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5(b) displays the variation of dielectric loss with frequencies for PCBDCy and BADCy. Dielectric loss is the function of the relaxation process which depends on the change in the viscoelastic nature of the polymer [30,31]. In the structure of PCBDCy, oxaspirocyclic segments decreased the crosslinking density, endowing the molecules with more flexibility and deformability, thus the activity of the chain segment increases, and the orientation of polar groups is less constrained by the chain segment, leading to 8…”
Section: Mechanical and Water Absorption Propertiesmentioning
confidence: 99%